Multi-frequency radiometer-based soil moisture retrieval and algorithm parameterization using in situ sites - Gao, Y.; Colliander, A.; Burgin, M.S.; Walker, J.P.; Dinnat, E.; Chae, C.; Cosh, M.H.; Caldwell, T.G.; Berg, A.; Martinez-Fernandez, J.; Seyfried, M.; Starks, P.J.; et al. (Remote sensing of environment, 2022)
L-band brightness temperature (TB) has been shown to provide the best sensitivity to soil moisture (SM) although C- and X-band based products offer a longer time-series from satellite-based measurements. Currently, global coverage SM is routinely produced from spaceborne measurements using all three frequency bands, but despite continued validation efforts of the products, the relative characteristics and performance of these observations have not been fully established. Therefore, this study focused on the parametrization of SM retrieval algorithms at L-, C- and X-bands using TB observations from the L-band radiometer on NASA's SM Active Passive (SMAP) mission and the C- and X-band channels of JAXA's Advanced Microwave Scanning Radiometer 2 (AMSR2) onboard the GCOM-W satellite. These can be applied in global SM retrieval algorithms using either one of the frequencies or a combination of them. The reference in situ SM data was obtained from 12 core validation sites across various land cover types around the world. The investigation highlighted the known challenges of retrieving SM from C- and X-band data compared to the higher sensitivity of the L-band data. Even with a site-specific retrieval algorithm parameterization, the mean correlation of the C- and X-band retrievals for the core validation site SM measurement were much lower than that for L-band, being 0.52 (0.54) and 0.45 (0.47) for vertical (horizontal) polarization, respectively, while for the L-band retrieval the corresponding values were 0.81 (0.77). The parameterization exercise showed that matching the C- and X-band TB measurements with an emission model was not difficult; the problem was relating the observations to SM under the influence of large roughness and vegetation effects. As a result, parameter optimization produced values for some sites that were not realistic or did not allow any practical sensitivity to SM at C- and X-band. Considering the L-band observations, the parameter optimization resulted in superior bias performance as compared to the operational SMAP product parameterization, but the sensitivity to SM changes (R and unbiased root mean square difference) did not improve markedly, or in some cases degraded at the expense of a smaller bias. •Spaceborne radiometer observation at L/C/X-band over 12 soil moisture core sites.•Calibration of soil moisture retrieval algorithm for L/C/X-band using the core sites.•L-band retrieval achieves correlation of 0.8 while C/X-band achieves only 0.5.•Retrieval capability of C/X-band questionable over some of the sites.•Calibration of L-band improves bias and RMSD over SMAP product but not sensitivity.